Ecological Footprint Awareness of Generation Z: A Case Study of Selçuk University Faculty of Science - Halil Osman Erbek; Yunus Akdoğan; Tenzile Erbayram (Journal of Advanced Research in Natural and Applied Sciences)
Achieving a sustainable ecosystem requires a harmonious relationship between biological capacity and ecological footprint. However, in today's rapidly industrializing world, population growth and lack of awareness about ecological footprints negatively impact biological capacity. Consequently, global ecological limits have been exceeded, straining the planet's carrying capacity. Human dominance over nature drives biodiversity loss and contributes to climate change, disrupting ecosystem balance, overconsuming natural resources, and causing environmental degradation. Industrialization and rapid urbanization have significantly increased resource consumption, leading to a sharp rise in greenhouse gas emissions—central to the carbon footprint and primary causes of climate change—that critically affect air quality, ecosystem stability, and biodiversity protection. Environmental factors directly influence human well-being, economic activities, and the health of all living organisms while reshaping the ecological order. This study aims to provide a fresh perspective on ecological awareness and inspire actionable steps in terms of building a sustainable ecosystem through a survey assessing the ecological literacy of Selcuk University Faculty of Science (SUFS) students. The survey reveals students' environmental awareness levels while examining its impact on their ecological behaviors. The general evaluation shows that SUFS students exhibit high awareness levels in the Ecological Footprint Awareness scale; however, scores related to recycling and transportation are lower than other dimensions. This indicates that targeted training for recycling and transportation is necessary to enhance overall awareness levels regarding ecological footprints. The findings will serve as a valuable resource for identifying strategies to improve environmental consciousness while emphasizing individuals' roles in fostering a sustainable future.